Das Speicherverhalten von 67Ga bei Erkrankungen der großen Kopfspeicheldrüsen - Bihl, H.; Maier, H. (Nuklearmedizin - NuclearMedicine, 1987)
ln a prospective study (59 patients) the pattern of 67Ga-uptake of the large salivary glands (LSG) in the course of typical disorders of the glands was investigated. Inflammatory and granulomatous disorders revealed - dependent on their acuity - an identical pattern of Ga-uptake. Extraglandular uptake was found in some instances of tuberculosis, sarcoidosis and myoepithelial sialadenitis. Among the benign LSG tumors all cystadeno- lymphomas showed intensive uptake while all pleomorphic adenomas did not. In 75% of the malignant LSG tumors Ga-uptake was pathologically increased, particularly in all adenocarcinomas of the series. 67Ga scintigraphy seems to be useful in the follow-up of inflammatory and granulomatous LSG disorders and in the differential diagnosis of pleomorphic adenoma versus cystadenolymphoma. Extraglandular uptake may give valuable hints for diagnostic work-up.